1998
DOI: 10.1152/ajpregu.1998.275.2.r418
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of skeletal muscle glycogen phosphorylase and PDH at varying exercise power outputs

Abstract: This study investigated the transformational and posttransformational control of skeletal muscle glycogen phosphorylase and pyruvate dehydrogenase (PDH) at three exercise power outputs [35, 65, and 90% of maximal oxygen uptake (V˙o 2 max)]. Seven untrained subjects cycled at one power output for 10 min on three separate occasions, with muscle biopsies at rest and 1 and 10 min of exercise. Glycogen phosphorylase in the more active ( a) form was not significantly different at any time across power outputs (21.4–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
142
3
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(170 citation statements)
references
References 38 publications
19
142
3
2
Order By: Relevance
“…Although the mechanisms of how exercise increases fat oxidation were not examined in this study, other researchers have demonstrated metabolic changes that occur with exercise treatment. Both enzyme levels and gene expression of enzymes that increase fat oxidation in skeletal muscle, such as lipoprotein lipase, triglyceride lipase, CPT-1, mitochondrial number, PDH kinase, fatty acid translocase/CD36, and fatty acid binding protein in the plasma membrane, have all been shown to increase with exercise (7,9,10,20,32).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of how exercise increases fat oxidation were not examined in this study, other researchers have demonstrated metabolic changes that occur with exercise treatment. Both enzyme levels and gene expression of enzymes that increase fat oxidation in skeletal muscle, such as lipoprotein lipase, triglyceride lipase, CPT-1, mitochondrial number, PDH kinase, fatty acid translocase/CD36, and fatty acid binding protein in the plasma membrane, have all been shown to increase with exercise (7,9,10,20,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, given that during high-intensity exercise malonylCoA concentration and ACC activity are at their nadir, it seems likely that factors other than changes in ACC activity and malonyl-CoA concentration must be involved for the shift in fuel utilization during intense exercise. These factors could include the following: 1) increased activation of glucose transport (30,31) and key enzymes of glycolysis (31), glycogenolysis (31,32), and glucose oxidation (e.g., pyruvate dehydrogenase) (32,33); 2) a reduction in the concentrations of carnitine, CoASH, or palmitoyl-CoA (33,34) and substrates that are necessary for fatty acid oxidation; and 3) inhibition of 3-ketoacyl-CoA thiolase, an enzyme involved in the ␤-oxidation of fatty acids (34). Another factor could be the shift from the use of type 1 to type 2b muscle fibers, which are more glycolytic and have a lower capacity for fatty acid oxidation during very intense exercise.…”
Section: Dean and Associatesmentioning
confidence: 99%
“…The demand of increased intensity may see a proportional reduction in uptake of circulating glucose while the stimulus for glucose perfusion is not diminished (seen by a continual rise in hepatic glucose output). This would be supported by [22], who noted a significant increase in the use of muscle glycogen created by fast oxidative/glycolytic fibre recruitment. The critical switch point between circulating glucose and muscle glycogen use may be the Gt.…”
Section: Heart Rate At Gt and Antmentioning
confidence: 77%
“…The rise in blood glucose observed with increasing exercise intensity may be the result of the increased percentage of muscle fibres recruited, and or the type of fibers recruited. An increase in the use of oxidative-glycolytic type II a [22] would increase the rate of glycolysis in the working muscle. This may also be linked to an increased rate of glucose oxidation prior to the rise in blood glucose.…”
Section: Resultsmentioning
confidence: 99%